1976
DOI: 10.1017/s0043174500063062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alachlor, Propachlor, and Prynachlor on GA3-induced Production of Protease and α-Amylase

Abstract: Alachlor [2-chloro-2′,6′-diethyl-N(methoxymethyl)-acetanilide], propachlor (2-chloro-N-isopropylacetanilide) and prynachlor [2-chloro-N-(1-methyl-2-propynyl)acetanilide], inhibited gibberellic acid (GA3),-induced production of protease and α-amylase in deembryonated barley (Hordeum vulgareL, ‘Schuyler’) seed. Production of protease was more sensitive to these herbicides than α-amylase. The degree of inhibition of protease and α-amylase production caused by alachlor was equivalent to that caused by cycloheximid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Numerous studies have been conducted to determine the mechanism of action of the a -chloroacetamides. Studies of photosynthesis (3,16), respiration (9,16,19), a-amylase synthesis (5,15,18,23), RNA synthesis (15), protein syn thesis (7,12,15), and lipid synthesis (6,23,24) have failed, however, to elucidate the primary mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been conducted to determine the mechanism of action of the a -chloroacetamides. Studies of photosynthesis (3,16), respiration (9,16,19), a-amylase synthesis (5,15,18,23), RNA synthesis (15), protein syn thesis (7,12,15), and lipid synthesis (6,23,24) have failed, however, to elucidate the primary mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies with certain a-chloroacetamides suggest they are inhibitors of protein synthesis (7,12,15), Pillai et al (17) found that, with metolachlor, leucine incorporation into protein was inhibited only at concentrations of 1 X 10" 4 M and higher. Inhibition of a-amylase synthesis in de-embryonated barley (Hordeum vulgare L.) seed by CDAA (N,Ndiallyl -2 -chloroacetamide) (15) and alachlor (5,18) has been reported. Using seed completely freed of contaminating microorganisms, however, Diner 3 found that a-amylase synthesis in de-embryonated 'Himalaya' barley was inhibited by alachlor and metolachlor only at concentrations in excess of 1 X 10' 3 M.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that these herbicides may act as repressors for gene action preventing the normal expression of the hormonal effect of GA 3 through the synthesis of DNA-dependent RNA. This was confirmed when higher levels of GA 3 overcame alachlor inhibition by removing the repressor effect [42].…”
Section: Hydrolytic Enzyme Activitiesmentioning
confidence: 78%
“…It was reported that propaclor inhibited the gibberellic acid (GA 3 ) induced production of αamylase in barley seeds [40]. Similarly, alachlor, propachlor and prynachlor were found to inhibit α-amylase as well as protease synthesis in barley seeds [41,42]. It was suggested that these herbicides may act as repressors for gene action preventing the normal expression of the hormonal effect of GA 3 through the synthesis of DNA-dependent RNA.…”
Section: Hydrolytic Enzyme Activitiesmentioning
confidence: 99%
“…It has been shown that interactions between site of absorption, herbicide placement and herbicide-soil relationships influence the selectivity of alachlor (Eshel, 1969;Jordan & Harvey, 1980). Rao & Duke (1976) found that early seedling development is inhibited by the acetanilides through root exposure, shoot exposure, or a combination of shoot and seed exposure, depending on the plant species. The main site at which sunflower absorbs soilapplied alachlor is apparently unknown.…”
mentioning
confidence: 99%